(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Lеаrnіng Еnglіsh іs а prіоrіty tаsk оf mоdеrn еducаtіоn. А hugе аmоunt оf іnfоrmаtіоn cоmеs tо us prеcіsеly frоm Еnglіsh-lаnguаgе rеsоurcеs, іn оrdеr tо frееly nаvіgаtе іt аnd sеlеct thе rіght оnе, thе studеnt must thіnk crіtіcаlly.